INCREASING VOCABULARY MASTERY THROUGH CONTRIVED LEARNING AT THE FIRST YEAR OF MTS 04 BLAGUNG BOYOLALI IN 2010/2011 ACADEMIC YEAR - FATMAWATI, ENDAH (2011)
This study is aimed at describing the procedure of increasing vocabulary mastery through contrived learning and knowing whether the technique can improve the students’ vocabulary mastery. In achieving the objective, the researcher used an action research involving four procedures; planning, acting observing, and reflecting. The research was held in MTS 04 Blagung Boyolali. The researcher took 40 students of the first year as the subject of the research. To collect the required data the researcher compared the results of pre-test, post-test 1 and post-test 2. In general the researcher concludes that the material in teaching vocabulary through contrived learning uses short story. The passages are chunk identification, completion, matching, word family identification, and rewriting exercises. From the result of the research, it can be concluded that contrived learning in MTS 04 Blagung Boyolali can increase the students’ vocabulary mastery. The results in this research are as follows: (1) There were 39 students who increased their English vocabulary achievement; (2) There was 1 student who decreased their English vocabulary achievement. It means that the teaching vocabulary through contrived learning is effective and helpful to improve the students’ vocabulary.